Improved medium-to-short-term earthquake predictions in China in 2022 - Huaizhong Yu; Rui Yan; Shiguang Deng; Jie Liu; Yan Xue; Gang Li; Mengyu Xie; Yuchuan Ma; Xiaotao Zhang; Yawei Ma; Yuan Zhengyi; Zeping Li (Geomatics, Natural Hazards & Risk)
Every year, China should determine annual seismic hazard regions for earthquakes of magnitude 5.0 and above in Mainland China in the next year. Meanwhile, the short-term earthquake potential in each seismic hazard region is evaluated by monthly analyzing geophysical observations in the same neighborhood and identifying anomalies therein. In 2022, China improved the strategies for these medium-to-short-term earthquake predictions. The annual seismic hazard regions are produced with the optimal methods selected by rigorous tests whose predictions are integrated through the Bayesian formula. And in short-term earthquake potential evaluation, in addition to tracking crucial anomalies, China pays attention to the changes in the number of observed anomalies. The practice in 2022 shows that more than 80% of earthquakes of magnitude 5.0 and above in Mainland China occurred in annual seismic hazard regions. Besides, the largest (Ms 6.9 Menyuan, Qinghai) and the most disastrous (Ms 6.8 Luding, Sichuan) earthquakes were predicted in both annual and short terms. Some crucial anomalies were observed before these two earthquakes, whose evolutions correlate well with the earthquake time and location. The statistics of the near-field geophysical observations indicate that, prior to the mainshock, the number of anomalies increased significantly and migrated toward the epicenter.